METHODS FOR THE EFFECTIVE DEVELOPMENT OF STUDENTS' LEXICAL AND GRAMMATICAL SKILLS (International journal of artificial intelligence, 2025)
This article analyzes methods for the effective development of students' lexical and grammatical skills. This issue, important for teachers, includes modern pedagogical approaches and methods, taking into account the difficulties that students face in the process of language learning. The article provides experiences in using interactive teaching methods, games, group work, and technologies that can be used to develop lexical and grammatical skills. It is also suggested that with the help of these methods, students can strengthen their interlingual communication and improve their ability to apply the language in practice. The main goal of the article is to identify innovative approaches that will help further strengthen students' language skills. As a result, the presented recommendations serve as a practical guide for language teachers and educational institutions.